Teacher’s translanguaging technique in vocational schools: does it influence EFL students’ competence? - Arif, Muhammad; Yulia, Yuyun; Hidayati, Sari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Translanguaging has emerged as a pivotal pedagogical approach, facilitating bilingual and multilingual practices that affirm the dynamic and flexible nature of language use in educational settings. This qualitative case study investigates the implementation of translanguaging techniques by an English teacher at Vocational High School 2 Wonosari. Data were collected through non-participant classroom observations and semi-structured interviews with a single teacher participant, selected through a purposive sampling. Thematic analysis of the data revealed that the teacher strategically employed translanguaging for key pedagogical functions, including concept explanation, instruction delivery, student motivation, and responsive feedback. These practices were further categorized into three distinct techniques: inter-sentential, intra-sentential, and tag translanguaging. From the teacher’s perspective, translanguaging served to diminish linguistic barriers, support vocabulary acquisition, and foster a more supportive and engaging classroom climate. The study concludes that translanguaging represents a strategic and effective pedagogical resource in multilingual EFL contexts, provided it is implemented flexibly and with sustained emphasis on target language exposure.